KEPATUHAN KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN TERDAFTAR PADA PASAR MODAL INDONESIA: DARI PERSPEKTIF HUKUM - Zulrahimah, Zulrahimah; Efendi, Rahmad; Zaitul, Zaitul (Gapenas Publisher, 2025)
This study aims to analyse the impact of financial reporting compliance on company financial performance, stock prices, and its relationship with the type of Public Accounting Firm (KAP) and business sector. Using a quantitative approach, this study observes 30 companies classified into two categories: compliant and non-compliant with financial reporting. The data used are secondary data obtained from the company's financial statements and other official sources. The analysis was conducted using descriptive statistics and the non-parametric Mann-Whitney U test to determine differences between groups. The research results show that companies that comply with financial reporting have a significantly higher Return on Assets (ROA) and stock prices compared to companies that do not comply. Hence, there is an indication that companies audited by the Big 4 Public Accounting Firms tend to be more compliant, although this relationship has not yet been statistically significant. On the contrary, no significant difference was found between business sectors and the level of reporting compliance. These findings support signalling theory and agency theory, indicating that compliance with financial reporting can be a significant indicator of a company's performance and reputation. This research provides practical implications for management, investors, and regulators regarding the importance of transparent and accountable financial reporting. However, the limited sample size and reliance on secondary data are concerns for future research. It is recommended that future studies consider a mixed-methods approach and additional variables to broaden the understanding of the determinants and impacts of financial reporting compliance.